BCSSE 2022: Expectations for Starting College in a Pandemic - Matthew Zivot:::::: (2022)
The Beginning College Student Survey (BCSSE) is a national survey, administered to 70,000+ first-time college students a year. The survey asks incoming students a range of questions about their experiences in high school and their thoughts about the coming year in college including topics such as study habits, in-class experiences, expectations for how they will overcome challenges, and intentions to interact with faculty, staff, and fellow students.At CSU Channel Islands (CSUCI), the BCCSE is administered as part of Freshman Island View Orientation (FIVO). While not all new students attend orientation and not all of those who attend orientation matriculate, the BCSSE response rate represents a very high proportion of our first-time freshmen (FTF) cohort, averaging at least 86.1% over the past four administrations1 with similar participation rates for students from historically underrepresented groups2 (85.4%) and non-HUG students (86.6%), first-generation students3 (86.1%) and continuing-generation students (86.2%), Pell grant eligible (84.7%) and non-Pell grant eligible (87.1%) students, as well as males (84.2%) and females (86.6%). This survey, therefore, provides a good window into the expectations of CSUCI's FTF and how that set of expectations has changed over time. This analysis will focus on changes between the Fall 2019 cohort, who started before the COVID-19 pandemic, and the Fall 2022 cohort, who experienced the pandemic for the last two and a half years of their high school career.